Sex hormones in Neurospora crassa. Spectrophotometric analysis cf the hormonal extracts of female sterile strains. - M. S. Islam; A. Nessa (Fungal Genetics Reports, 1980)
Sex hormones in Neurospora crassa. Spectrophotometric analysis cf the hormonal extracts of female sterile strains.